Diagnostic study of the maize-based system in South and East Africa: pathways to sustainable intensification and diversification - a case study of Chipata and Monze districts in Zambia - Mwale, M. (International Water Management Institute (IWMI), 2024)
Efficient agricultural water management is key to improving crop-water productivity. Very few smallholder farmers in Zambia use irrigation as it is largely informal and applied to fruits and vegetables grown close to the water sources. Only 1% of the small holder farmers use irrigation for field crops and about 16% of them use it for fruits and vegetables (Ngoma, et.al, 2017).